A Modified Weber Number Capturing the Bouncing–Wetting Transition of Droplet Impact on Rough Surfaces (Adv. Mater. Interfaces 10/2023). Issue 10 (4th April 2023) - Bao, Yanyao; Wang, Zhongzheng; Shi, Zhang; Gan, Yixiang
Abstract : Droplet Dynamics Yanyao Bao and colleagues report on the spreading and bouncing modes of droplets impacting on rough surfaces. The results in article number 2201873 suggest that a higher surface area and roughness promote the transition from bouncing to wetting of a droplet, benefiting surface design for facilitating droplet non‐adhesion features during transport. (Design credit: Dr. Louis Ong)